A rare case of unruptured live second trimester ovarian ectopic pregnancy - Choudhary, Saroj; Singh, Preksha T.; Bhati, Indra; Deora, R. K. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Ovarian ectopic pregnancy is an extreme rare entity in all the cases of ectopic pregnancies. Before, the end of first trimester, it usually ends with rupture. It is such a unique and rare presentation that only 3% of all ectopic pregnancies are reported due to an ovarian cause. In this case report, authors have presented a patient with ovarian ectopic pregnancy which was found unruptured, live at the second trimester. The patient presented with abdominal pain and after routine check-up and ultrasound abdomen, patient was taken for an emergency explorative laparotomy and the ovarian pregnancy was excised and sent for histopathological examination, the histopathological examination further confirmed the diagnosis of the same. In some researches it has been seen that ovarian pregnancies are rising, considering that, the findings of the report may help frame future diagnostic and treatment guidelines.